Identity Management Systems Analysis : Botswana Country Report - Republic of Botswana (World Bank, Washington, DC, 2017)
This report analyses the identity management system (IMS) of the Republic of Botswana with respect to: (1) accessibility, (2) robustness, (3) integration and regulated access to data, and (4) legal frameworks and data protection, and documents the extent to which the legal and institutional framework and the human and physical infrastructures have facilitated the establishment, operationalization, and management of identity management as a comprehensive system. Botswana has a single foundational IMS is a primary tool for public administration and governance as well as facilitation of service delivery to the public. It creates one identity per person pursuant to the current legal framework which is used several times by the person at various institutions to facilitate the individual’s access to services including social safety net programs, claiming of rights, and entitlements. The national identity card is used as a breeder document for obtaining other documents such as passports, driver’s licenses, and voter registration cards. The national identity number used at age 16 is the same unique identification number (UID) issued upon registration of birth. This strategy ensures an identity life cycle from identity establishment to end of identity. The national identity management system is linked with other systems, such as the electoral system, the social benefit registration system (SOBERS), government payroll, and the transport system. Similarly, through this link, the national IMS is updated in real time when a death occurs. It is envisaged that the identity management (ID-M) system will in the future be linked to the immigration and citizenship system under the department of immigration and citizenship to progress it to a fully-fledged population register or people hub.